Optimization performance management with FCAPS and ITILv3: opportunities and obstacles - Adityas Widjajarto; Muharman Lubis; M. K. Rizal Syahputra (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
With the need for rapidly growing network services each year; the factors of reliability, availability and quality become extremely critical for organizations, groups, institutions and governments to have in the network services implementation. In this case, several rural governments requires the improvement of its network performance management in establishing their internal and external operation to align with the grand design by the central government in improving citizen’s satisfaction through public service. Testing was done using scenarios for output analysis and packet loss as parameters. The results of the proposed topology obtained a productivity of 541.43 Kbps and a packet loss of 0.07%. While the current topology gets a rate of 421.28 Kbps and packet loss of 0.22%. It can be concluded that the proposed topology is still better than the current topology. The optimization of performance management is based on the FCAPS method which emphasize in the performance monitoring and data analysis with the support of ITILv3 that contains documentation and policy guidance to conduct quality performance management. In addition, performance management activities will occur with processes in the design of ITIL services and existing conditions.